Safe and adjustable mineralized carbon rod and preparation method thereof
By mixing activated natural ore powder with activated porous ore powder and surface treatment, combined with modified activated carbon, a safe and adjustable mineralized carbon rod is formed, which solves the problem of unstable release of mineralized carbon rods and achieves minerals Multi-stage sustained release and healthy water supply meets national standards and has high safety and long service life.
Patent Information
- Application Number
- CN202411019479.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-29
AI Technical Summary
The existing mineralized carbon rods are unable to effectively adsorb and fix natural rocks due to the lack of internal particle pores, resulting in unstable mineral release and short service life, which makes them unable to provide truly healthy mineral water.
By mixing activated natural ore powder with activated porous ore powder, surface treatment is carried out, combined with modified activated carbon, a safe and adjustable mineralized carbon rod is formed to achieve multi-stage sustained release and stable release of minerals.
实现了矿物质的平稳溶出和缓慢释放,提高了饮用水的微量元素含量,满足国家标准,并具有高安全性和长使用寿命,同时能够有效去除全氟辛酸等新型污染物。
Smart Images

Figure CN119118276A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mineralized filter elements, and in particular to a safe and adjustable mineralized carbon rod and a preparation method thereof. Background Art
[0002] Water is an indispensable substance in people's lives. Mineral water contains a certain amount of minerals and trace elements, such as calcium, magnesium, potassium, etc. These minerals and trace elements are important components required by the human body and play an important role in maintaining life activities, maintaining water and electrolyte balance, and promoting bone growth. Therefore, drinking water healthily is particularly important.
[0003] Water purifiers can provide residents with safe drinking water. They mainly purify and improve the taste through PP cotton filter elements, activated carbon filter elements, RO membrane filter elements and post-carbon filter elements. As consumers' demand for healthy water increases, some mineralized materials are usually filled in the post-carbon filter element, that is, natural ore particles are filled into the post-carbon filter element to form a mineralized filter element. Natural rocks can release chemical elements and minerals, mineralize the water body, increase the mineralization of raw water, and restore pure water to healthy water rich in minerals.
[0004] However, the existing mineralized carbon rods cannot effectively adsorb and fix natural rocks due to the poor porosity of the internal particles, resulting in unstable release of minerals. Usually, the effect is strong in the initial stage of use, with a large amount of dissolution, but the effect is weak or even no effect in the later stage. The mineralization effect is general and the service life is short, resulting in the inability to provide truly healthy mineral water. Summary of the invention
[0005] Based on this, it is necessary to provide a safe and adjustable mineralized carbon rod and a preparation method thereof.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: A method for preparing a safe and adjustable mineralized carbon rod comprises the following steps:
[0007] Mixing activated natural ore powder and activated porous ore powder to obtain composite mineralized powder;
[0008] The composite mineralized powder and the first binder are mixed and granulated to obtain composite mineralized particles;
[0009] Performing surface treatment on the composite mineralized particles to obtain modified composite mineralized particles;
[0010] The modified composite mineralized particles, modified activated carbon and a second binder are mixed and molded to obtain a safe and adjustable mineralized carbon rod.
[0011] In one embodiment, when the activated natural ore powder and the activated porous ore powder are mixed, the activated natural ore powder and the activated porous ore powder are mixed in a mass ratio of 1-20:1.
[0012] In one embodiment, the activated natural ore powder is one or more of activated strontium-rich sedimentary rock, activated limestone, activated dolomite, activated Iceland spar and activated magnesite.
[0013] In one embodiment, the activated porous mineral powder is activated zeolite or activated volcanic rock.
[0014] In one embodiment, when the composite mineralized powder and the first binder are mixed, the composite mineralized powder and the first binder are mixed in a mass ratio of 6-12:1.
[0015] In one embodiment, the surface treatment of the composite mineralized particles comprises:
[0016] The composite mineralized particles are surface treated with a surfactant.
[0017] In one embodiment, the surfactant is 0.5%-2% of silane coupling agent KH550 or 0.5%-2% of silane coupling agent KH570.
[0018] In one embodiment, the mixing of the modified composite mineralized particles, the modified activated carbon and the second binder comprises:
[0019] By mass, 5-30 parts of the modified composite mineralized particles, 40-60 parts of the modified activated carbon and 25-40 parts of the second binder are mixed.
[0020] In one embodiment, the method for treating modified activated carbon comprises:
[0021] Pre-treating activated carbon;
[0022] Performing secondary activation on the pretreated activated carbon;
[0023] The surface of the activated carbon after secondary activation is chemically modified to obtain modified activated carbon.
[0024] The present invention also provides a safe and adjustable mineralized carbon rod, which is prepared by the preparation method of the safe and adjustable mineralized carbon rod described in any one of the above embodiments.
[0025] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a safe and adjustable mineralized carbon rod, wherein the activated natural ore powder, the activated porous ore powder and the first binder are mixed and granulated to obtain composite mineralized particles, the activated porous ore powder can adsorb the activated natural ore powder, so that the minerals can be dissolved smoothly, and the first sustained release of the minerals is achieved, and then the composite mineralized particles are surface treated to further control the dissolution amount of the minerals, and the second sustained release of the minerals is achieved, and finally the safe and adjustable mineralized carbon rod is obtained by mixing with modified activated carbon and the second binder, and the modified activated carbon has better pore structure and surface chemical properties, high chemical stability and thermal stability, and can be used under different environmental conditions. Maintaining good adsorption performance, it can not only effectively adsorb the modified composite mineralized particles, control their single release amount, and play the role of three-time slow release of minerals, but also reduce the resistance when the fluid passes through. At the same time, it can also have a good removal effect on new PFAS pollutants represented by PFOA. The prepared safe and adjustable mineralized carbon rod can effectively and slowly release elements such as strontium, calcium and magnesium during continuous water flow to make drinking water composite mineralized, and the release amount maintains dynamic balance within a certain range, which not only increases the content of trace elements in drinking water, but also meets the national limit standards for trace elements in natural drinking mineral water. It can effectively remove perfluorooctanoic acid in drinking water, with high safety and long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 A schematic diagram of a process for preparing a safe and adjustable mineralized carbon rod according to an embodiment of the present invention;
[0028] Figure 2 It is a curve chart of the TDS increase value of composite mineralized powder soaking;
[0029] Figure 3 It is a curve diagram of strontium dissolution amount when composite mineralized powder is immersed;
[0030] Figure 4 It is a curve chart of the TDS increase value of composite mineralized powder soaking;
[0031] Figure 5 It is a curve diagram of strontium dissolution amount when composite mineralized powder is immersed;
[0032] Figure 6It is a curve chart of calcium dissolution amount of composite mineralized powder after immersion;
[0033] Figure 7 It is a curve chart of magnesium dissolution amount after immersion of composite mineralized powder;
[0034] Figure 8 It is a curve chart of the added value of TDS of composite mineralized particles soaked;
[0035] Fig. 9 It is a curve chart of strontium dissolution amount after immersion of composite mineralized particles;
[0036] Fig.10 It is a curve chart of calcium and magnesium dissolution amount after immersion of composite mineralized particles;
[0037] Fig.11 It is a curve chart of the tds increase value after soaking the modified composite mineralized particles;
[0038] Fig.12 It is a curve diagram of strontium dissolution amount after immersion of modified composite mineralized particles;
[0039] Fig.13 It is a curve diagram of the calcium and magnesium dissolution amount after immersion of modified composite mineralized particles;
[0040] Fig.14 This is a curve diagram of the strontium content of the flushing water of the formed carbon rod;
[0041] Fig.15 This is a curve chart of the calcium and magnesium content in the flushing water of the formed carbon rod. DETAILED DESCRIPTION
[0042] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0044] In one embodiment, Figure 1 As shown, a method for preparing a safe and adjustable mineralized carbon rod comprises the following steps:
[0045] Step 110, mixing activated natural ore powder and activated porous ore powder to obtain composite mineralized powder.
[0046] In this embodiment, when the activated natural ore powder and the activated porous ore powder are mixed, the activated natural ore powder and the activated porous ore powder are mixed in a mass ratio of 1-20:1, and the activated porous ore powder can effectively adsorb the activated natural ore powder, so that the minerals in the activated natural ore powder can be dissolved smoothly. The activated natural ore powder is one or more of activated strontium-rich sedimentary rock, activated limestone, activated dolomite, activated Iceland spar and activated magnesite, and the activated porous ore powder is activated zeolite or activated volcanic rock. The type of activated natural ore powder and the content of different types of activated natural ore powder can be selected according to the needs of composite mineralization of drinking water.
[0047] In one embodiment, the activation method of natural ore powder is: first crush the natural ore, then rinse it repeatedly with pure water, dry it, and then sieve it into 35-100 mesh powder, soak the powder in an activation treatment solution for activation for 4-8 hours, the activation treatment solution is a mixed solution of potassium hydroxide and potassium sulfate, take out the powder, put it in an oven at 250-350°C for high-temperature activation treatment, and obtain activated natural ore powder.
[0048] In one embodiment, the activation method of the activated porous ore powder is: first crush the porous ore, then rinse it repeatedly with pure water, and then screen the powder into 35 mesh-100 mesh after drying, and soak the powder in an activation treatment solution for activation for 4-12 hours. The activation treatment solution is a mixed solution of dilute hydrochloric acid and potassium chloride. After taking out the powder, put it into an oven at 250-350°C for high-temperature activation treatment to obtain activated porous ore powder.
[0049] Step 120: Mix the composite mineralized powder and the first binder, and granulate to obtain composite mineralized particles.
[0050] In this embodiment, the first binder is one of polyvinyl alcohol, polyvinyl butyral and silica sol, and the composite mineralized powder and the first binder are mixed in a mass ratio of 6-12:1, so that the activated natural ore powder and the activated porous ore powder can be mixed and granulated to obtain composite mineralized particles.
[0051] In one embodiment, the activated strontium-rich sedimentary rock and the activated zeolite are mixed in a mass ratio of 1-5:1 to obtain low-mineralized composite mineralized particles.
[0052] In one embodiment, activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite are mixed in a mass ratio of 3-6:4-12:1-2:1 to obtain highly mineralized composite mineralized particles.
[0053] Step 130: performing surface treatment on the composite mineralized particles to obtain modified composite mineralized particles.
[0054] In this embodiment, the composite mineralized particles are surface treated with a surfactant, wherein the surfactant is a silane coupling agent and a hydrophobic agent, which can reduce the wettability of the surface of the composite mineralized particles and further control the dissolution amount of minerals in the composite mineralized particles.
[0055] In one embodiment, the surfactant is 0.5%-2% of silane coupling agent KH550 or 0.5%-2% of silane coupling agent KH570. Specifically, silane coupling agent KH550 has amino and ethoxy groups in its molecules, and silane coupling agent KH570 has methacryloyloxy functional groups and three hydrolyzable methoxy functional groups in its molecules, both of which can improve the binding force between the composite mineralized particles and the organic polymer material, thereby improving the water resistance of the composite mineralized particles, further controlling the dissolution amount of minerals, and helping to improve the dispersibility of the composite mineralized particles in the organic polymer material, and can release the minerals in the composite mineralized particles more evenly.
[0056] Step 140: Mix the modified composite mineralized particles, modified activated carbon and a second binder to form a safe and adjustable mineralized carbon rod.
[0057] In this embodiment, the second binder is a high molecular weight polyethylene rubber powder. When the modified composite mineralized particles, modified activated carbon and the second binder are mixed, 5-30 parts of the modified composite mineralized particles, 40-60 parts of the modified activated carbon and 25-40 parts of the second binder are mixed by mass. The modified activated carbon can effectively adsorb the modified composite mineralized particles and control their single release amount. The safe and adjustable mineralized carbon rod prepared can activate the minerals in the natural ore powder in a multi-stage slow-release manner, with high safety and long service life.
[0058] In one embodiment, the treatment method of the modified activated carbon includes: pre-treating the activated carbon, performing secondary activation on the pre-treated activated carbon, and performing surface chemical modification on the activated carbon after the secondary activation to obtain modified activated carbon. Specifically, when pre-treating the activated carbon, the activated carbon is screened according to the particle size, for example, 40-60 mesh activated carbon is screened, and then the screened activated carbon is washed to remove impurities and dust on the surface of the activated carbon to improve the purity of the activated carbon. When the pre-treated activated carbon is secondary activated, the pre-treated activated carbon is exposed to a high-temperature gas environment at 250-300°C, which can further change the pore structure and surface properties of the activated carbon and improve its adsorption performance. When the surface chemical modification of the activated carbon after the secondary activation is performed, the activated carbon is oxidized and modified using a strong oxidant such as hydrogen peroxide, nitric acid or chloric acid to change the functional groups and chemical properties on the surface of the activated carbon, which can increase the number of oxygen-containing functional groups on the surface of the activated carbon, thereby improving its adsorption capacity.
[0059] In this embodiment, by modifying the activated carbon, the modified activated carbon can have better pore structure and surface chemical properties, high chemical stability and thermal stability, and can maintain good adsorption performance under different environmental conditions. It can not only effectively adsorb the modified composite mineralized particles, control its single release amount, and play a role in three slow releases of minerals, which can reduce the resistance of the fluid passing through. At the same time, it can also remove PFAS (Per-and polyfluoroalkyl substances, perfluoro or polyfluoroalkyl compounds) represented by PFOA (Perfluorooctanoic Acid), and the removal rate can reach more than 99%. It is worth noting that perfluoro and polyfluoroalkyl compounds PFAS are new pollutants, known as "permanent chemicals" and "toxic time bombs", and have been included in the "List of New Pollutants under Key Control (2023 Edition)". Removing PFAS new pollutants represented by PFOA is an important part of the current development of water purification.
[0060] The present invention also provides a safe and adjustable mineralized carbon rod, which is prepared by the preparation method of the safe and adjustable mineralized carbon rod described in any of the above embodiments. During the continuous water flow process, elements such as strontium, calcium and magnesium can be effectively and slowly released to allow complex mineralization of drinking water, and the release amount maintains a dynamic balance within a certain range, which not only increases the content of trace elements in drinking water, but also meets the national limit standards for trace elements in natural drinking mineral water. It can activate minerals in natural ore powders by multi-stage slow release, and can effectively remove new PFAS pollutants represented by PFOA in drinking water. It has high safety and long service life.
[0061] Compared with the prior art, the present invention has at least the following advantages:
[0062] The present invention provides a method for preparing a safe and adjustable mineralized carbon rod, wherein the activated natural ore powder, the activated porous ore powder and the first binder are mixed and granulated to obtain composite mineralized particles, the activated porous ore powder can adsorb the activated natural ore powder, so that the minerals can be dissolved smoothly, and the first slow release of the minerals is achieved, and then the composite mineralized particles are surface treated to further control the dissolution amount of the minerals, and the second slow release of the minerals is achieved, and finally the safe and adjustable mineralized carbon rod is obtained by mixing with modified activated carbon and the second binder, wherein the modified activated carbon has better pore structure and surface chemical properties, high chemical stability and thermal stability, and can maintain good The adsorption performance can not only effectively adsorb the modified composite mineralized particles, control their single release amount, and play the role of three-time slow release of minerals, but also reduce the resistance when the fluid passes through. At the same time, it can also have a good removal effect on new PFAS pollutants represented by PFOA. The prepared safe and adjustable mineralized carbon rod can effectively and slowly release elements such as strontium, calcium and magnesium during the continuous water flow process to make drinking water composite mineralized, and the release amount maintains dynamic balance within a certain range. It not only increases the content of trace elements in drinking water, but also meets the national limit standards for trace elements in natural drinking mineral water. It can effectively remove perfluorooctanoic acid in drinking water, with high safety and long service life.
[0063] The present invention is further described below with specific examples.
[0064] Example 1
[0065] A composite mineralized powder is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 1:1, wherein the activated natural ore powder is activated strontium-rich sedimentary rock, and the activated porous ore powder is activated zeolite.
[0066] Example 2
[0067] A composite mineralized powder is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1, wherein the activated natural ore powder is activated strontium-rich sedimentary rock, and the activated porous ore powder is activated zeolite.
[0068] Example 3
[0069] A composite mineralized powder is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 5:1, wherein the activated natural ore powder is activated strontium-rich sedimentary rock, and the activated porous ore powder is activated zeolite.
[0070] Example 4
[0071] A composite mineralized powder, activated natural ore powder and activated porous ore powder are mixed in a mass ratio of 10:1, the activated natural ore powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, and the activated porous ore powder is activated zeolite.
[0072] The mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:4:2:1.
[0073] Example 5
[0074] A composite mineralized powder is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 10:1, the activated natural ore powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, and the activated porous ore powder is activated zeolite.
[0075] The mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:1:1.
[0076] Example 6
[0077] A composite mineralized powder is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 20:1, the activated natural ore powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, and the activated porous ore powder is activated zeolite.
[0078] The mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 6:12:1:1.
[0079] Example 7
[0080] A composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1 to obtain the composite mineralized powder, and by mixing and granulating the composite mineralized powder and a first binder in a mass ratio of 8:1 to obtain the composite mineralized powder.
[0081] The activated natural ore powder is activated strontium-rich sedimentary rock, the activated porous ore powder is activated zeolite, and the first binder is polyvinyl butyral.
[0082] Example 8
[0083] A composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1 to obtain the composite mineralized powder, and by mixing and granulating the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain the composite mineralized powder.
[0084] The activated natural ore powder is activated strontium-rich sedimentary rock, the activated porous ore powder is activated zeolite, and the first binder is polyvinyl butyral.
[0085] Example 9
[0086] A composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 10:1 to obtain the composite mineralized powder, and by mixing and granulating the composite mineralized powder and a first binder in a mass ratio of 8:1 to obtain the composite mineralized powder.
[0087] Among them, the activated natural ore powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, the activated porous ore powder is activated zeolite, the mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:1:1, and the first binder is polyvinyl butyral.
[0088] Example 10
[0089] A composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 10:1 to obtain the composite mineralized powder, and by mixing and granulating the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain the composite mineralized powder.
[0090] Among them, the activated natural ore powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, the activated porous ore powder is activated zeolite, the mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:1:1, and the first binder is polyvinyl butyral.
[0091] Embodiment 11
[0092] A modified composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1 to obtain composite mineralized powder, then mixing the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and finally performing surface treatment with a surfactant to obtain the modified composite mineralized particles.
[0093] The activated natural ore powder is activated strontium-rich sedimentary rock, the activated porous ore powder is activated zeolite, the first binder is polyvinyl butyral, and the surfactant is 0.5% silane coupling agent KH570.
[0094] Example 12
[0095] A modified composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1 to obtain composite mineralized powder, then mixing the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and finally performing surface treatment with a surfactant to obtain the modified composite mineralized particles.
[0096] The activated natural ore powder is activated strontium-rich sedimentary rock, the activated porous ore powder is activated zeolite, the first binder is polyvinyl butyral, and the surfactant is 1% silane coupling agent KH570.
[0097] Embodiment 13
[0098] A modified composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1 to obtain composite mineralized powder, then mixing the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and finally performing surface treatment with a surfactant to obtain the modified composite mineralized particles.
[0099] The activated natural ore powder is activated strontium-rich sedimentary rock, the activated porous ore powder is activated zeolite, the first binder is polyvinyl butyral, and the surfactant is 2% silane coupling agent KH570.
[0100] Embodiment 14
[0101] A modified composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 10:1 to obtain composite mineralized powder, then mixing and granulating the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and finally performing surface treatment with a surfactant to obtain the modified composite mineralized particles.
[0102] Among them, the activated natural mineral powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, the activated porous mineral powder is activated zeolite, the mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:1:1, the first binder is polyvinyl butyral, and the surfactant is 0.5% silane coupling agent KH550.
[0103] Embodiment 15
[0104] A modified composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 10:1 to obtain composite mineralized powder, then mixing and granulating the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and finally performing surface treatment with a surfactant to obtain the modified composite mineralized particles.
[0105] Among them, the activated natural ore powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, the activated porous ore powder is activated zeolite, the mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:1:1, the first binder is polyvinyl butyral, and the surfactant is 1% silane coupling agent KH550.
[0106] Example 16
[0107] A modified composite mineralized particle is obtained by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 10:1 to obtain composite mineralized powder, then mixing and granulating the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and finally performing surface treatment with a surfactant to obtain the modified composite mineralized particles.
[0108] Among them, the activated natural mineral powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, the activated porous mineral powder is activated zeolite, the mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:1:1, the first binder is polyvinyl butyral, and the surfactant is 2% silane coupling agent KH550.
[0109] Embodiment 17
[0110] A safe and adjustable mineralized carbon rod is prepared by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1 to obtain composite mineralized powder, then mixing the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and using a surfactant to perform surface treatment on the composite mineralized particles to obtain modified composite mineralized particles. Finally, the modified composite mineralized particles, modified activated carbon and a second binder are mixed to obtain a safe and adjustable mineralized carbon rod with a specification of 30×12×180 mm.
[0111] Among them, the activated natural ore powder is activated strontium-rich sedimentary rock, the activated porous ore powder is activated zeolite, the first binder is polyvinyl butyral, the surfactant is 1% silane coupling agent KH570, the second binder is high molecular polyethylene rubber powder, the mass fraction of modified composite mineralized particles is 15 parts, the mass fraction of modified activated carbon is 50 parts and the mass fraction of the second binder is 30 parts.
[0112] Embodiment 18
[0113] A safe and adjustable mineralized carbon rod is prepared by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 10:1 to obtain composite mineralized powder, then mixing the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and using a surfactant to perform surface treatment on the composite mineralized particles to obtain modified composite mineralized particles. Finally, the modified composite mineralized particles, modified activated carbon and a second binder are mixed to obtain a safe and adjustable mineralized carbon rod with a specification of 30×12×180 mm.
[0114] Among them, the activated natural mineral powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, the activated porous mineral powder is activated zeolite, the mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:1:1, the first binder is polyvinyl butyral, the surfactant is 1% silane coupling agent KH550, the second binder is high molecular polyethylene rubber powder, the mass fraction of modified composite mineralized particles is 15 parts, the mass fraction of modified activated carbon is 50 parts and the mass fraction of the second binder is 30 parts.
[0115] Comparative Example 1
[0116] A composite mineralized powder is an activated natural ore powder having a corresponding mass fraction in Example 1, wherein the activated natural ore powder is an activated strontium-rich sedimentary rock.
[0117] Comparative Example 2
[0118] A composite mineralized powder, wherein the activated natural ore powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, and the mass ratio of the activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:2.
[0119] Comparative Example 3
[0120] A mineralized carbon rod is prepared by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1 to obtain composite mineralized powder, then mixing the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and finally mixing the composite mineralized particles, modified activated carbon and a second binder to obtain a safe and adjustable mineralized carbon rod with a specification of 30×12×180 mm.
[0121] Among them, the activated natural ore powder is activated strontium-rich sedimentary rock, the activated porous ore powder is activated zeolite, the first binder is polyvinyl butyral, the second binder is high molecular polyethylene rubber powder, the mass fraction of composite mineralized particles is 15 parts, the mass fraction of modified activated carbon is 50 parts and the mass fraction of the second binder is 30 parts.
[0122] Comparative Example 4
[0123] A mineralized carbon rod is prepared by mixing activated natural ore powder and activated porous ore powder in a mass ratio of 3:1 to obtain composite mineralized powder, then mixing the composite mineralized powder and a first binder in a mass ratio of 9:1 to obtain composite mineralized particles, and finally mixing the composite mineralized particles, modified activated carbon and a second binder to obtain a safe and adjustable mineralized carbon rod with a specification of 30×12×180 mm.
[0124] Among them, the activated natural mineral powder is activated strontium-rich sedimentary rock, activated limestone and activated magnesite, the activated porous mineral powder is activated zeolite, the mass ratio of activated strontium-rich sedimentary rock, activated limestone, activated magnesite and activated zeolite is 3:5:1:1, the first binder is polyvinyl butyral, the second binder is high molecular polyethylene rubber powder, the mass fraction of composite mineralized particles is 15 parts, the mass fraction of modified activated carbon is 50 parts and the mass fraction of the second binder is 30 parts.
[0125] The composite mineralized powders of Examples 1-6 and Comparative Examples 1-2 were soaked in deionized water for 1-24 hours, and the increase in the total amount of soluble solids, i.e., the increase in TDS and the amount of strontium dissolved were tested. The calcium and magnesium dissolved amounts of the composite mineralized powders of Examples 4-6 and Comparative Example 2 were tested. The test results are shown in Tables 1-6 and Figure 2-7 shown.
[0126] Deionized water was used to test the increase in the total amount of dissolved solids, i.e., the increase in TDS and the dissolution of strontium, calcium and magnesium, of the composite mineralized particles of Examples 7-10. The test results are shown in Tables 7-9 and Figure 8-10 shown.
[0127] Deionized water was used to test the increase in the total amount of dissolved solids, i.e., the increase in TDS and the dissolution of strontium, calcium and magnesium, of the composite mineralized particles of Examples 11-16. The test results are shown in Tables 10-12 and Figure 11-13 shown.
[0128] Deionized water was used to perform a flushing test on the safe and adjustable mineralized carbon rods of Examples 17-18 and the mineralized carbon rods of Comparative Examples 3-4. The flushing test flow rate was 2L / min and the flushing was 30min. The sanitary safety and strontium content of the flushing water were tested. The calcium and magnesium contents of the flushing water of Example 18 and Comparative Example 4 were tested. The test results are shown in Tables 13-15 and Figure 14-15 shown.
[0129] The safe and adjustable mineralized carbon rods with a specification of 30×12×180 mm prepared in Example 17 were subjected to a PFOA removal test, and perfluorooctanoic acid with a purity of 98% was spiked throughout the process.
[0130] Table 1 TDS increase value of composite mineralized powder soaking
[0131]
[0132]
[0133] Table 2 Strontium dissolution amount of composite mineralized powder soaked
[0134]
[0135] Table 3 TDS increase value of composite mineralized powder immersion
[0136]
[0137] Table 4 Strontium dissolution amount of composite mineralized powder soaked
[0138]
[0139]
[0140] Table 5 Calcium dissolution amount of composite mineralized powder after immersion
[0141]
[0142] Table 6 Magnesium dissolution amount of composite mineralized powder soaked
[0143]
[0144]
[0145] Table 7 TDS increase value of composite mineralized particles soaked
[0146]
[0147] Table 8 Strontium dissolution amount of composite mineralized particles soaked
[0148]
[0149] Table 9 Calcium and magnesium dissolution from composite mineralized particles
[0150]
[0151]
[0152] Table 10 TDS increase of modified composite mineralized particles after soaking
[0153]
[0154] Table 11 Strontium dissolution amount of modified composite mineralized particles after immersion
[0155]
[0156]
[0157] Table 12 Calcium and magnesium dissolution from modified composite mineralized particles after immersion
[0158]
[0159] Table 13 TDS added value of hygienic and safe immersion of molded carbon rods
[0160]
[0161] Table 14 Strontium content of formed carbon rod flushing water
[0162]
[0163]
[0164] Table 15 Calcium and magnesium content of carbon rod flushing water
[0165]
[0166] Table 16 Test results of calcium and magnesium content in formed carbon rods for PFOA removal
[0167] Flow rate(L) Raw water (ng / L) Filtered water (ng / L) Removal rate (%) 5 405 0 100 1500 410 0 100 3000 403 0 100 4500 412 2 99.5 6000 406 3 99.3
[0168] As can be seen from Tables 1 to 16, the safe and adjustable mineralized carbon rod prepared by the preparation method of a safe and adjustable mineralized carbon rod provided by the present invention can adsorb activated natural ore powder by activating porous ore powder, so that the minerals can be dissolved smoothly, realizing the primary slow release of minerals, and surface treating the composite mineralized particles to further control the dissolution amount of minerals, realizing the secondary slow release of minerals, and finally, by mixing with modified activated carbon and a second binder, it can effectively adsorb the modified composite mineralized particles, control the single release amount, and play the role of slow release of minerals three times, and can effectively and slowly release elements such as strontium, calcium and magnesium during the continuous water flow process to make drinking water composite mineralized, and the release amount maintains dynamic balance within a certain range, which not only increases the content of trace elements in drinking water, but also meets the national limit standards for trace elements in natural drinking mineral water, and can also remove new PFAS pollutants represented by PFOA, and the removal rate can reach more than 99%, with high safety and long service life.
[0169] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0170] The above-mentioned embodiments only express several embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of this application shall be based on the attached claims.
Claims
1. A method for preparing a safe and adjustable mineralized carbon rod, characterized in that: The following steps are involved: Mixing activated natural ore powder and activated porous ore powder to obtain composite mineralized powder; The composite mineralized powder and the first binder are mixed and granulated to obtain composite mineralized particles; Performing surface treatment on the composite mineralized particles to obtain modified composite mineralized particles; The modified composite mineralized particles, modified activated carbon and a second binder are mixed and molded to obtain a safe and adjustable mineralized carbon rod.
2. The method for preparing a safe and adjustable mineralized carbon rod according to claim 1, characterized in that: When the activated natural ore powder and the activated porous ore powder are mixed, the activated natural ore powder and the activated porous ore powder are mixed at a mass ratio of 1-20:
1.
3. The method for preparing a safe and adjustable mineralized carbon rod according to claim 2, characterized in that: The activated natural ore powder is one or more of activated strontium-rich sedimentary rock, activated limestone, activated dolomite, activated Iceland spar and activated magnesite.
4. The method for preparing a safe and adjustable mineralized carbon rod according to claim 3, characterized in that: The activated porous ore powder is activated zeolite or activated volcanic rock.
5. The method for preparing a safe and adjustable mineralized carbon rod according to claim 1, characterized in that: When the composite mineralized powder and the first binder are mixed, the composite mineralized powder and the first binder are mixed in a mass ratio of 6-12:
1.
6. The method for preparing a safe and adjustable mineralized carbon rod according to claim 1, characterized in that: The surface treatment of the composite mineralized particles comprises: The composite mineralized particles are surface treated with a surfactant.
7. The method for preparing a safe and adjustable mineralized carbon rod according to claim 6, characterized in that: The surfactant is 0.5%-2% of silane coupling agent KH550 or 0.5%-2% of silane coupling agent KH570.
8. The method for preparing a safe and adjustable mineralized carbon rod according to claim 1, characterized in that: The modified composite mineralized particles, the modified activated carbon and the second binder are mixed, comprising: By mass, 5-30 parts of the modified composite mineralized particles, 40-60 parts of the modified activated carbon and 25-40 parts of the second binder are mixed.
9. The method for preparing the safe and adjustable mineralized carbon rod according to claim 8, characterized in that: The treatment method of the modified activated carbon comprises: Pre-treating activated carbon; Performing secondary activation on the pretreated activated carbon; The surface of the activated carbon after secondary activation is chemically modified to obtain modified activated carbon.
10. A safe and adjustable mineralized carbon rod, characterized in that: The safe and adjustable mineralized carbon rod is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Fenton reaction ferrous slow-release particle
CN110615518A
Activated carbon rod for improving taste of drinking water
CN111530418A
Extrusion molding strontium mineralization filter element and preparation method thereof
CN112919850A
Activated carbon composite filter element for pure water remineralization as well as preparation method and application of activated carbon composite filter element
CN117883880A
Cited By
Multi-element self-assembled slow-release composite mineralized material as well as preparation method and application thereof
CN121426272A
Slow-release metasilicic acid mineralization material, filter element and preparation method
CN121517222A
